Soulless Matter, Seats of Energy. Metals, Gems and Minerals in South Asian Tradition, edited by Fabrizio M. Ferrari and Thomas W. P. Dähnhardt. (17th April 2019) - Smith, Frederick
Abstract : Soulless Matter, Seats of Energy. Metals, Gems and Minerals in South Asian Tradition, edited by Fabrizio M. Ferrari and Thomas W. P. Dähnhardt. Sheffield: Equinox, 2016. xxxii + 282 pp., £22.95/29.95 (pb). ISBN 978-1-78179-129-5.